Sustainable Destination Management In India: Perception Of Stakeholders On Sustainability Of Kerala Tourism - Venugopalan, T. (Archives of Business Research, 2021)
This research paper explores the economic, environmental, and socio-cultural sustainability of tourist destinations in Kerala, a southern state of India, from the perspective of tourists, based on primary research. The exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM) are utilized for examining and analysing the sustainability of the tourist destination of Kerala. The research findings on environmental pressure validate that tourism has been exerting huge pressure on the environment. The environment management mechanisms adopted by the government and tourism industry have been effective in mitigating the adverse environmental impacts of tourism. Tourism has been succeeded in achieving economic sustainability by empowering the local communities. Destination governance mechanisms are directly contributing to destinations’ sustainability. The research findings also establish that tourism development in Kerala is socially and culturally sustainable. Thus, this research concludes that tourism development is ensuring the environmental, economic, and social sustainability of tourist destinations of Kerala.